Effects of labor taxes on hours of market and home work: The role of international capital mobility and trade - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 2014)
This paper evaluates the Prescott (2004) hypothesis that permanently higher payroll taxes fully explain the decline in number of market hours worked in Europe (relative to America) over three decades. The Prescott model made assumptions that, in steady state, left out any incentive for either international capital mobility or international exchange of goods. We study a one-good model where the imposition of higher payroll taxes in one region leads to higher domestic real interest rate in that region. As a result, there are incentives for international capital outflows into the high payroll tax region with the consequence that number of market hours worked in the low payroll tax region also decline. With identical tastes and rate of time discount across the two regions, we find that the number of hours worked in the market, home work, and leisure are equalized across the two regions. In the multi-good model, when factor price equalization holds so free trade acts as a substitute for factor mobility, we show that there is also equalization of market work, home work, and leisure across the two regions.